Targeted silencing of GNAS in a human model of osteoprogenitor cells results in the deregulation of the osteogenic differentiation program - Elli, Francesca Marta; Mattinzoli, Deborah; Ikehata, Masami; Bagnaresi, Francesca; Maffini, Maria A.; Del Sindaco, Giulia; Pagnano, Angela; Lucca, Camilla; Messa, Piergiorgio; Arosio, Maura; Castellano, Giuseppe; Alfieri, Carlo M.; et al. (Frontiers in Endocrinology, 2024)
Introduction The dysregulation of cell fate toward osteoprecursor cells associated with most GNAS-based disorders may lead to episodic de novo extraskeletal or ectopic bone formation in subcutaneous tissues. The bony lesion distribution suggests the involvement of abnormal differentiation of mesenchymal stem cells (MSCs) and/or more committed precursor cells. Data from transgenic mice support the concept that GNAS is a crucial factor in regulating lineage switching between osteoblasts (OBs) and adipocyte fates. The mosaic nature of heterotopic bone lesions suggests that GNAS genetic defects provide a sensitized background for ectopic osteodifferentiation, but the underlying molecular mechanism remains largely unknown. Methods The effect of GNAS silencing in the presence and/or absence of osteoblastic stimuli was evaluated in the human L88/5 MSC line during osteodifferentiation. A comparison of the data obtained with data coming from a bony lesion from a GNAS-mutated patient was also provided. Results Our study adds some dowels to the current fragmented notions about the role of GNAS during osteoblastic differentiation, such as the premature transition of immature OBs into osteocytes and the characterization of the differences in the deposed bone matrix. Conclusion We demonstrated that our cell model partially replicates the in vivo behavior results, resulting in an applicable human model to elucidate the pathophysiology of ectopic bone formation in GNAS-based disorders.